KARAKTERISASI FISIKOKIMIA IKAN BAGE (MAKANAN TRADISIONAL SUMBAWA) MENGGUNAKAN OVEN PENGERING - Isworo, Rhestu; Nuraisyah, Anni (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
Lemuru production in Sumbawa has increased and is one of the processed productsthe famous one is bage fish. This bage fish is processed by a process of salting andpickling, then drying and frying. Request from the Sumbawa peopleThere are already many who want to bring this typical bage fish souvenir from the region. Bytherefore in this study a controlled drying process was carried out usingoven, and is expected to be a solution to improve the quality of bage fishphysicochemical and microbiological. The results showed that fresh lemuru hadthe average moisture content was 86%, protein content was 19.8%, fat content was 6.1%. Water contentThe highest bage fish was found in treatment with a temperature of 50 Â° C for 2 hours (56.33%)while the lowest water content is found in 4 hours drying with a temperature of 60 Â° C(28.41%). The highest TPC test value was obtained in bage fish drying at 50oCfor 2 hours, which is 21000 CFU / gr (2.1 x 104 CFU / gr).